Manuell markberedning med kultivatoraggregat - Ahlm, Jonathan (SLU/School for Forest Management, 2019)
The purpose of this work is to chart the spruce plants ability to stay strong against one of the biggest problems connected with reforestation. This is a survey that has been done in order to see if there are other ways to protect the plants from the pine weevil than the conventional alternatives. This survey includes 800 plants that has been planted with different methods in order to chart the extent of damage made from pine weevil. A literature study has been done and concludes the knowledge about the ecology and biology about the pine weevil, extra focused on the reproduction and the diet. A chapter about how the industry handles the widespread problem primary with treated plants, mostly in combination with some kind of preparation, in this study we have tried a new type of preparation made with a cultivator aggregate and a chainsaw on a manually way. The conclusions of the study is telling that it is better to use the manually method instead of using nothing at all. With the economic aspect in mind it is also better to do the smaller areas before the bigger, the smaller the better.